Integrasi Nilai-Nilai Islam dan Praktik Manajemen Kontemporer - Nasution, Siti Zahra Amelia Putri; Rialdy, Novien (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This journal discusses the integration of Islamic values into contemporary management practices, highlighting the importance of Islamic economics in a global context. By emphasizing principles such as justice, trustworthiness, and balance between the world and the hereafter, this article shows how Islamic management can be implemented to create an effective and ethical organization. The application of these values is not only relevant to achieving business goals, but also to building an inclusive and sustainable work environment.